Design and Development of the Rescentify Website as a Platform to Support Product Marketing - Indrayana, I Kadek Wanna; Putra, I Gede Juliana Eka; Putra, Ida Bagus Ardhi (Primakara University, 2026)
The rapid development of digital technology has encouraged businesses to utilize websites as a primary medium for marketing and information dissemination. Rescentify, a business engaged in environmentally friendly products, requires a digital platform capable of introducing its products, building customer trust, and expanding its marketing reach. Therefore, this study focuses on the design and development of the Rescentify website as a digital information and marketing platform using the Prototype method. This method involves iterative stages, including communication, quick planning, quick design, prototype construction, and delivery and feedback, allowing user requirements to be effectively identified and implemented.The developed website incorporates key features such as a homepage, product catalog, detailed product descriptions, a scent recommendation system (Scent Advisor) based on user mood, article pages, and integrated communication through WhatsApp for transaction purposes. The website design emphasizes a simple and user-friendly interface to enhance usability and accessibility for a wide range of users. In addition, Search Engine Optimization (SEO) techniques and social media integration are applied to improve website visibility and expand digital marketing reach. The results of system testing using the Black Box method indicate that all features function as intended and meet the predefined system requirements. The implementation of the Rescentify website demonstrates its effectiveness as a promotional and information platform, facilitating easy access to product information and improving interaction between customers and the business. Therefore, the website is expected to support more optimal, efficient, and sustainable digital marketing activities, particularly for environmentally friendly products